Gruppenaufnahme (1979)
Vorsitzender CDU-Landesverband Hessen Alfred Dregger; Vorsitzender CDU-Landesverband Rheinland Heinrich Köppler; CDU-Generalsekretär Heiner Geißler; CDU-Vorsitzender Helmut Kohl;